Effects of Low Knowledge on Anemia, Weight Gain, and Chronic Energy Deficiency in Pregnant Women - Sudarmi, Sudarmi; Pranajaya, Pranajaya; Riyanto, Riyanto (Poltekkes Kemenkes Tanjung Karang, Indonesia, 2023)
Introduction: High risks of pregnancy, such as anemia, chronic energy deficiency, and hypertension at risk of emergencies, can be prevented. However, its prevalence is still high. This situation is triggered by a low of information and low knowledge of pregnant women. Purpose: This study was to analyze the effect of the knowledge level of pregnant women with the incidence of anemia, chronic energy deficiency, weight gain, and hypertension as a high risk of pregnancy. Method: A cross-sectional study was used to design this study involving 74 pregnant women selected according to inclusion criteria. A questionnaire measuring tool to collect data on the mother's level of knowledge about the high risk of pregnancy and the incidence of high risk of pregnancy: anemia, lack of protein-energy, weight gain, and hypertension. Analysis of bivariate data using a chi-square test with a confidence level of 0.05. Results: Low knowledge in high-risk pregnant women about one-third (34%), anemia 28.4%, chronic energy deficiency 18.9%, weight gain more than 14.9%, and hypertension 8.1%. Low knowledge of pregnant women affects the incidence of high risk of pregnancy with anemia (p=0.013; OR=3.996), weight gain (p= 0.004; OR=13.44), and chronic energy deficiency (p=0.012; OR=3.778). Meanwhile, the incidence of hypertension does not indicate any association (p = 0.084) Conclusion: Less knowledgeable pregnant women contribute to an increased incidence of high-risk pregnancy and pregnancy complications. Efforts to educate about high-risk and pregnancy complications need to be increased by innovating the development of easy and affordable educational methods, such as online media to increase maternal knowledge. Latar belakang: Risiko tinggi kehamilan, seperti anemia, kekurangan energi kronik dan hipertensi berisiko mengalami kegawatdaruratan, dapat di cegah. Namun, kenyatannya prevalensinya masih tinggi. Keadaan ini dipicu oleh kurang informasi dan pengetahuan kurang pada ibu hamil. Tujuan: Studi ini untuk menganalisis pengaruh tingkat pengetahuan ibu hamil dengan kejadian anemia, kekurangan energi kronis, peningkatan berat badan, dan hipertensi sebagai risiko tinggi kehamilan. Metode: Studi cross sectional digunakan sebagai desain penelitian ini yang melibatkan 74 ibu hamil yang dipilih sesuai kriteria inklusi. Alat ukur kuesioner untuk mengumpulkan data tingkat pengetahuan ibu tentang risiko tinggi kehamilan dan kejadian risiko tinggi kehamilan: anemia, kekurangan energi kronik, penambahan berat badan dan hipertensi. Analisis data bivariat menggunakan uji chi square dengan tingkat kepercayaan 0,05. Hasil: Pengetahun rendah pada ibu hamil risiko tinggi sekitar sepertiga (34%), mengalami anemia 28,4%, kekurangan energi kronik 18,9%, penambahan berat badan lebih 14,9%, dan hipertensi 8,1%. Pengetahuan rendah ibu hamil berpengaruh terhadap kejadian risiko tinggi kehamilan dengan anemia (p=0.013; OR=3.996), kenaikan berat badan (p=0.004; OR=13.44) dan kekurangan energi kronik (p=0.012; OR=3.778). Sedangkan, kejadian hypertensi tidak menunjukkan ada hubungan (p=0.084). Simpulan: Ibu hamil yang berpengetahuan kurang berkontribusi pada kejadian peningkatan kejadian risiko tinggi kehamilan dan komplikasi kehamilan. Upaya edukasi risiko tinggi dan komplikasi kehamilan perlu ditingkatkan dengan inovasi pengembangan metode edukasi yang mudah dan terjangkau, seperti media online untuk meningkatkan pengetahuan ibu.